A study on thermal characteristics of phase change material (PCM) in gypsum board for building application - D., Rozanna; Ahmad, Salmiah; Chuah, T. G.; R., Medyan; Choong, Thomas S. Y.; M., Sa'ari (Malaysian Palm Oil Board, 2005)
Using fatty acids as phase change materials (PCMs), it is possible to store a large amount of thermal energy in a small mass and with a narrow temperature transition. Passive solar heating and cooling can be done by three methods – simple immersion, direct incorporation and encapsulation. This study investigated the effect of using a lauric-stearic acids eutectic mixture at 75.5:24.5 w/w as PCM in gypsum board. The eutectic mixture had a melting point of 34.1ºC and latent heat of 171.1 kJ kg-1 respectively. Gypsum boards were immersed 1 hr in PCM and the thermal characteristics before and after immersion were investigated. The 12.5 mm board absorbed 38.0% PCM and differential scanning calorimetry (DSC) showed that the melting point and latent heat were 34.0ºC and 50.28 kJ kg-1 , respectively. For 6 mm board, PCM absorption was 39.2% with the melting point of 34.0ºC and the latent heat of 52.87 kJ kg-1 . From the results, the thermal characteristics of the PCM-gypsum boards were similar to those of the PCM.